Analisis Pengaruh Kandungan Informasi Komponen Laba Dan Rugi Terhadap Koefisien Respon Laba (Erc) Studi Empiris Pada Perusahaan Manufaktur Sektor Industri Dasar Dan Kimia Yang Terdaftar Di Bursa Efek Indonesia (Bei) - Amanda, Annisa Lutvy; Efrianti, Desi; Marpaung, Bintang `Sahala (Jurnal Ilmiah Manajemen Kesatuan, 2019)
The income statement can be a reliable decision-making material, if the income statement has a valuable information content. Profit (loss) information is said to be valuable if the information contained in the income statement causes the movement of market reaction. The market reaction is indicated by a change in the price of the relevant securities which is typically measured using the stock return as the value of the change. Return or share price in response to earnings information can be measured using earnings response coefficient or ERC (Earnings Responses Coeffficient). The purpose of this research is to analyze the influence of each independent variable that is PEPS, LEPS, PORD, LORD, POP, LOP, PFIN, LFIN, PEXT, LEXT, TAX and Book Value control variable to dependent variable that is Coefficient of Profit Response (ERC) . This research was conducted on 33 companies manufacturing basic industry sectors and chemicals in 2012 until 2015. Supporting data used are financial statements obtained from www.idx.co.id in the year 2012-2015. From the research that has been done show that the variables of PEPS, PORD, POP, PEXT have information content that influence to earnings response coefficient (ERC) while LEPS, LORD, LOP, PFIN, LFIN, LEXT, TAX do not have information content that influence to coefficient Profit response (ERC).